Analysis of Determinants of Profitability of Insurance Companies in Indonesia Listed on the Indonesia Stock Exchange for the Period 2019–2024 - Marjihad Luthfiyah Rahma (JURNAL ECONOMINA, 2026)
This study examines profitability determinants of insurance companies listed on the Indonesia Stock Exchange during 2020–2023 using agency theory. Profitability is proxied by return on assets (ROA). Key explanatory variables include premium growth, investment yield, and loss ratio, with controls for firm age, expense ratio, firm size, and board size. Panel data regression is employed to test their effects on ROA. The study highlights that higher premiums and investment income do not necessarily translate into higher profits without cost efficiency and effective governance mechanisms that mitigate agency problems.